Visual Processing Matters in Chinese Reading Acquisition and Early Mathematics - Yang, Xiujie; Meng, Xiangzhi (Frontiers in Psychology, 2020)
The main purpose of the present study is to investigate whether visual processing uniquely contributes to early academic development, namely character reading and early mathematics, in Chinese children. Eighty-two Chinese kindergarteners at K3 (Mean age=68 months, SD=0.30) were followed up to grade one (Mean age=82 months, SD=0.35) with an interval of 14 months. Nonverbal intelligence, inhibitory control, sustained attention, character reading, and mathematics were measured at kindergarten. Character reading and mathematics were assessed again at grade one. Results showed visual processing at kindergarten significantly predicted character reading at grade one after controlling age, gender, nonverbal IQ, inhibitory control, sustained attention and initial reading performance. Similarly, visual processing at kindergarten explained unique variance in early mathematics at grade one when other cognitive measures and initial mathematics at kindergarten were controlled. These findings suggest that visual processing should serve as a domain-general precursor of children's character reading acquisition and early mathematics and therefore is common underlying factor of later academic learning.